Nutrients dynamics in corn-Brachiaria intercropping systems - Oliveira, Silas Maciel de (2018)
Corn (Zea mays L.) intercropped with Brachiaria spp. plays an important role in tropical agriculture management, providing residues or forage to areas intensively cropped. Although previous studies provide useful information about effects of intercropping on soil management and crop yield, a better understanding of how corn-Brachiaria intercropping systems impacts exogenous and endogenous nutrient dynamic is needed. Two experiments were performed in the both conventional and late planting season. In the first, corn and palisadegrass (Brachiaria brizantha cv. Marandu) monoculture were compared with two intercropping patterns, directed for production of residues or forage, with simulated animal grazing. Biomass, crop nitrogen (N) content, N derived from fertilizer and N budget were measured. Among farming systems, variable responses remained almost unchanged during period of simultaneous growth. After corn harvest, intercropping patterns achieved greater biomass (0.6-11 Mg ha-1) and N content (12-318 kg ha-1) relative to fallow preceded by corn monoculture, but it results in overall gains (pre and post-harvest) only to conventional planting season. N fertilizer recovery was not affected by intercropping patterns. When corn and Brachiaria were intercropped to establish pasture, simulated grazing after grain harvest had a tightly influence on N budget, approximately -221 kg ha-1. The second experiment investigated the influence of Brachiaria species on corn nutrients partitioning and their cycling after corn harvest. Biomass, N, phosphorus (P) and potassium (K) content were evaluated using corn intercropped with three species of Brachiaria (B. Brizantha cv Marandu, B. ruziziensis, and B. hybrid cultivar Mulato II, Convert HD 36) and corn monoculture. Biomass and nutrient content was not affect when corn was intercropped with Brachiaria species. After corn harvest, Brachiaria nutrient content and biomass yield were ranking from greater to lower following the order: B. brizantha > B. ruziziensis > B. convert. Relative with the corn monoculture, intercropping treatments enhanced the total biomass (corn + Brachiaria) and the nutrient accumulation only when planted at conventional season. Over 6 site-yr, benefits of intercropping appear after corn harvest, particularly at conventional planting season. Corn intercropped with Brachiaria species either had no effect N fertilizer recovery or affect N-fertilizer distribution within components of soil-plant system. Nonetheless, intercropping provide greater biomass accumulation after harvest compared with corn monoculture, resulting in larger nutrient content stored in plant component. Our results suggest a larger N requirements when crop-livestock activities was integrated. Corn intercropped with B. brizantha during conventional season was the best approach to enhanced crop yield and nutrient cycle for corn production systems.